2019
DOI: 10.1093/ecco-jcc/jjz176
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IL-6 Exacerbates Colitis and Induces Systemic Inflammation in IL-10-Deficient Mice

Abstract: Abstract Background and Aims Interleukin 6 [IL-6] or its receptor is currently a candidate for targeted biological therapy of inflammatory bowel disease [IBD]. Thus, a comprehensive understanding of the consequences of blocking IL-6 is imperative. We investigated this by evaluating the effects of IL-6 deletion on the spontaneous colitis of IL-10-deficient mice [IL-10−/−]. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…This is an important feature, especially in the role portrayed by AAM in restraining the excessive inflammatory immune response and promoting tissue repair [ 5 ]. Several studies support our findings, demonstrating that mice with a deficient AAM polarization expressed higher susceptibility to colitis [ 6 , 45 , 46 ]. This is in accordance with the notion that polarized AAM drives a directionally concordant expansion of regulatory T cells to establish mucosal tolerance and protect against colitis [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…This is an important feature, especially in the role portrayed by AAM in restraining the excessive inflammatory immune response and promoting tissue repair [ 5 ]. Several studies support our findings, demonstrating that mice with a deficient AAM polarization expressed higher susceptibility to colitis [ 6 , 45 , 46 ]. This is in accordance with the notion that polarized AAM drives a directionally concordant expansion of regulatory T cells to establish mucosal tolerance and protect against colitis [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…IL-10 plays an important role in UC. Previous studies [ 12 , 16 ] revealed that intestinal inflammation may be aggravated in individuals with IL-10 deficiency through inhibition of regulatory T cells/cytotoxic T-lymphocyte-associated protein 4 and through promotion of the IL-1β/T helper 2 cell pathway. Studies have shown that IL-10 can negatively regulate CXCL8 , CXCL1 , IL-1 β, CCL20 , and PTGS2 [ 17 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Il ‐ 10 −/− model is the closest animal model to the CD phenotype. 21 We investigated the clinical results and effective mechanisms of Epac‐2 in Il ‐ 10 −/− mice treated with Me‐cAMP (an Epac‐2 agonist) or HJC‐0350 (an Epac‐2 antagonist). Colonic expression of Epac‐2 was abnormal in CD patients, and Epac‐2 activated the Rap‐1 pathway and inhibited the phosphorylation of NF‐κB/MAPK in macrophages, which increased the levels of ZO‐1 and occludin in intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%